Application of the Environmental Impact Classification for Alien Taxa (EICAT) to a global assessment of alien bird impacts. Issue 9 (10th July 2016) - Evans, Thomas; Kumschick, Sabrina; Blackburn, Tim M.
Abstract: Aim: To apply the recently published EICAT protocol to an assessment of the magnitude of environmental impacts of alien bird species established world‐wide. Location: Global. Methods: A review of published literature and online resources was undertaken to collate information on the reported environmental impacts of 415 bird species with self‐sustaining alien populations world‐wide. The resulting data were then categorized following the EICAT guidelines and analysed using R. Results: Environmental impact data were found for approximately 30% of species with alien populations. Most alien birds had low impacts, categorized as either minimal concern (MC ) or minor (MN ). However, 37 bird species had moderate (MO ) impacts or above, including five with massive (MV ) impacts. Almost half of all impacts identified related to competition between alien birds and native species. Impact magnitudes were non‐randomly distributed: impacts due to predation tended to be more severe than for other impact mechanisms, and impacts on oceanic islands tended to be more severe than for other regions, but impacts associated with Psittaciform species tended to be less severe than for other alien bird orders. Approximately 35% of assessments were allocated a 'low' confidence rating. Main conclusions: The EICAT protocol can be effectively applied to categorize and quantify the impacts of all alien species within an entire taxonomic class. The results demonstrate significant variation in both the type and severity of impacts generated by alien birds. However, we found no data regarding the environmental impacts of the great majority of alien bird species, and where impact data were available, our assessments were frequently allocated a 'low' confidence rating. Our work therefore identifies major data gaps that will help influence the direction of future invasive alien species impact research.